2022
DOI: 10.3390/cells11111737
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Metabolism Pathway Is Involved in the Control of Glucose Homeostasis: A Cystathionine Beta Synthase Deficiency Study in Mouse

Abstract: Cystathionine beta synthase (CBS) catalyzes the first step of the transsulfuration pathway from homocysteine to cystathionine, and its deficiency leads to hyperhomocysteinemia (HHcy) in humans and rodents. To date, scarce information is available about the HHcy effect on insulin secretion, and the link between CBS activity and the setting of type 2 diabetes is still unknown. We aimed to decipher the consequences of an inborn defect in CBS on glucose homeostasis in mice. We used a mouse model heterozygous for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Interestingly, the livers of streptozotocin-induced diabetic rats exhibit a marked increase in CBS mRNA levels [107]. A recent experimental study in mice showed that knockout of the CBS gene impairs stimulated insulin secretion and sensitivity [108], suggesting the importance of the transsulfuration pathway in insulin secretion and overall glucose homeostasis. Cystathionine gamma-lyase (CTH) is an enzyme that catalyzes the last step in the transsulfuration pathway by cleaving the L,L-cystathionine molecule into L-cysteine, part of which is utilized for the biosynthesis of glutathione [109].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the livers of streptozotocin-induced diabetic rats exhibit a marked increase in CBS mRNA levels [107]. A recent experimental study in mice showed that knockout of the CBS gene impairs stimulated insulin secretion and sensitivity [108], suggesting the importance of the transsulfuration pathway in insulin secretion and overall glucose homeostasis. Cystathionine gamma-lyase (CTH) is an enzyme that catalyzes the last step in the transsulfuration pathway by cleaving the L,L-cystathionine molecule into L-cysteine, part of which is utilized for the biosynthesis of glutathione [109].…”
Section: Discussionmentioning
confidence: 99%
“…The second is an impaired synthesis of cystathionine from L-serine and homocysteine by cystathionine β-synthase and a subsequent decrease in the drain of homocysteine from the methionine cycle to the transsulfuration pathway ( Figure 2 ). The possibility is supported by the presence of hyperhomocysteinemia in humans and rodents with cystathionine β-synthase deficiency [ 49 ].…”
Section: L-serine and Diabetesmentioning
confidence: 99%
“…tabolism pathways were identified in our insulinoma analysis due to mutations in APOB -the main apolipoprotein of chylomicrons and LDL, and genes involved in the metabolism of homocysteine, CTH (converts cystathionine derived from methionine into cysteine) and MTHFR (homocysteine remethylation to methionine). The proper homeostasis of homocysteine has been shown to be significant for controlling insulin secretion and action [68,69].…”
Section: Original Papermentioning
confidence: 99%